Analysis of Social Protection Coverage in Tarakeshwor Municipality, Kathmandu - Gautam, Nar Hari; Barnawal, Nitu (Journal of Social Protection, 2023)
Social security allowances is a major social protection strategy in Nepal which consists of senior citizen allowances, support to widows, single women, children under-five from Karnali region, Dali children under-five, disable persons, and people from endangered communities including Raute, and Chepang. This study aims to analyse the coverage of social security in Tarakeswhor Municipality of Kathmandu in terms of process, implementation, perception and utilisation of allowances. Findings show that 90 per cent of recipients are satisfied with the delivery of the services. Similarly, 84.5 percent of them wished to keep cash at home to fulfill their daily needs. Likewise, 91.8 per cent of them felt easy during processing. Among110 respondents, 27 of them were late for enrollment due to lack of communication. This suggests that, there is still need of awareness and knowledge dissemination in this municipality to increase the coverage. Even though the amount is small, it has helped most of the beneficiaries to manage their expenditure at home and few of them felt honored as the government took care of them.